In Vitro Effect of Rifampin on Mycobacteria - Lorian, Victor (1969)
Rifampin inhibited 20 strains of Mycobacterium tuberculosis in concentrations of 0.005 to 0.02 μg/ml in 7H-9 broth with Tween 80 and killed all or nearly all of the inoculum in four to eight times greater concentrations. In the same medium without Tween 80, as well as on 7H-10 agar, about 16 to 64 times these amounts were required to produce the same effect. Rifampin was also active against M. kansasii and some of the nonchromogenic mycobacteria. The incidence of mycobacterial cells resistant to rifampin within the cultures studied was in the range of one to four per 10(8) to 10(9) colony-forming units with concentrations of 4 to 125 μg of rifampin per ml. Only one of the Battey cultures and that of M. fortuitum yielded cells resistant to rifampin at 125 μg/ml but not at 500 μg/ml. The same strains yielded more than double that number of organisms resistant to streptomycin and up to 100 times more organisms resistant to isoniazid. All three drugs stopped the growth or reduced the mycobacterial population in growing cultures after contact for 24 to 48 hr. Complete inhibition of growth was produced by rifampin at 1.0 μg/ml in an average of 6 days and by streptomycin at 5.0 μg/ml in 3 days. After an average contact of 10.7 days with rifampin, five of seven strains resumed growth and all strains began regrowth after exposure to streptomycin for 9.4 days. The marked susceptibility of M. tuberculosis and of atypical mycobacteria to rifampin in vitro and the relatively low incidence of resistant mutants suggests that this agent may have clinical usefulness in the treatment of tuberculosis and some other mycobacterioses.